Проблемы создания компьютерных систем с применением наноэлементной базы - Палагин, А.В.; Боюн, В.П.; Яковлев, Ю.С. (Управляющие системы и машины, 2017)
Показан перечень проблем с их взаимосвязями при переходе элементной базы на уровень нанотехнологии. Определены особенности нанотехнологии каждого типа (молекулярной, оптической – фотонной, квантовой, ДНК, НЭМС, МЭМС), порождающие эти проблемы. Разработан фрагмент онтологии, устанавливающий взаимосвязи между указанными проблемами. Сформулированы направления для их решения. Показано перелік проблем з їх взаємозв'язками під час переходу елементної бази на рівень нанотехнологiї. Визначено особливості нанотехнології кожного типу (молекулярної, оптичної – фотонної, квантової, ДНК, НЕМС, МЕМС), що породжують ці проблеми. Розроблено фрагмент онтології, що встановлює взаємозв'язки між вказаними проблемами. Сформульовано напрями для їх вирішення. The purpose. In connection with necessity of increasing the productivity of computer systems at the expense of the sizes of elements reduction, the computers constructed on the fourth generation element base have appeared incapable. The further reduction of the solid-state element base executed on chips of the big integrated schemes (BIS) cannot render the essential influence on increasing the systems productivity as the sizes of elements come nearer to the atomic. There was a necessity of transition to the fifth generation element base, which is executed in nanotechnology. In this connection the purpose can be formulated as follows: to show the list of problems with their interrelations at transition of element base to the nanotechnology level and to define the features of each type nanotechnology (molecular, optical - photon, quantum, neural, DNA), generating these problems. Thus, the ontology fragment is developed, establishing interrelations between the specified problems. The directions for their decision are formulated. Examples of concrete scopes using the separate products executed on nanotechnology are presented where their use shows the greatest effect. Methods. We used the methods of the modern status analysis of every specified type of the element base executed in nanotechnology, and the problems, which are subject to the decision while creation the units and blocks using such element base. Thus, the ontological approach is applied for establishing the interrelations between the problems. Result. Peculiarities of each type of nanotechnology (molecular, optical - photon, quantum, neural, DNA) are allocated, generating the problems which are necessary for solving while creation the units and blocks, and also the computers using element base, executed in nanotechnology. The ontology fragment is developed, establishing interrelations between these problems.